Wings of Fire : A guide to the dragon world - Sutherland, Tui, 1978- (Sutherland, Tui, 1978- Wings of fire., 2023)
"Dive into the world of Wings of Fire like never before! The #1 New York Times, USA Today, and Wall Street Journal bestselling Wings of Fire series soars to even greater heights with an all-new collection of stories and art from readers' favorite dragon world! Tui T. Sutherland and Wings of Fire cover artist Joy Ang delve deeper into the legends of the ten dragon tribes, creating the ultimate collection for every FanWing. Each chapter of A Guide to the Dragon World explores the history, mythology, and folklore of the beloved series in a truly spectacular and gift-worthy edition!"--